P091 Osteoid osteoma of the trapezoid bone: a diagnostic pitfall of a wrist chronic monoarthritis. (11th November 2021) - Rym, Fakhfakh; Baccouche, Khadija; Elamri, Nejla; Laataoui, Sadok; Zegaloui, Hela; Bouajina, Elyes
Abstract: Background: Osteoid osteoma is a benign bone tumor representing ∼10% of all benign bone tumors. Although osteoid osteoma of the long bones is usual, the location in the carpus, especially, in the trapezoid bone is rare [1, 2]. The Objective is toreport a case of osteoid osteoma of the trapezoid bone with extension to the adjacent second metacarpal bone that was missed diagnosis at initial presentation. Methods: We describe the clinical, radiological features and outcomes after surgical resection. Results: A 24-year-old right-handed female, presented with a three-year history of pain at the left wrist, particularly, in the radial-side. She didn't report any trauma to the wrist. The pain increased over time. She couldn't use her hand in daily activities and could hardly sleep because of increasing pain at night. Before being referred to our department, she consulted a surgeon. She was treated with oral anti-inflammatory drugs, steroids, several intraarticular steroid injections without relieving pain. The Magnetic resonance imaging (MRI) showed bone marrow oedema in the trapezium and the trapezoid bone, synovial effusion, and tenosynovitis of the flexors of the thumb. A synovectomy was performed and the histopathology revealed non-specific chronic inflammation. One year later in our department, examination showed wrist swelling, tenderness and pain on palpation. The erythrocyte sedimentation rate was 12 mm/h and the mean C-reactive protein was 2 mg/l. Autoantibodies testing were negative. Initial radiography was read as normal. Initially, Naproxen (550 mg/day) and Morphine (60 mg/day) were prescribed with partially relieving pain. Scintigraphy showed increased uptake of 99mTc in the radial-side of the left wrist. Then, a bone tumor was suspected. The Computed tomography (CT) images revealed a well-demarcated sclerotic nidus surrounded by a halo of radiolucent osteoid tissue, consistent with an osteoid osteoma of the trapezoid bone and the adjacent second metacarpal bone. Surgical resection of the osteoid osteoma was performed. Histopathological examination confirmed the diagnosis. The patient reported complete pain relief since her surgery. She had no recurrence to date. Conclusion: Osteoid osteoma should be in the differential diagnosis list of chronic wrist pain/arthritis. In this case, careful attention is necessary for patients unresponsive to treatment with long-lasting symptoms. If radiographs are inconclusive, CT or MRI should be considered to better visualize the nidus of osteoid osteoma in the small bones of the hand.